Coaching Training - Chen, Chris (Association for Talent Development, 2003)
Coaching Training focuses on helping coaches properly define their coaching roles and provides the skills needed for success. A wide range of activities fall under the label of coachingguiding, teaching motivating, and mentoringand this book is designed to train for one-on-one coaching situations. Find the best advice for choosing training session content, sample training agendas, and step-by-step preparation and training delivery instructions.